A Case of Cold Urticaria Mistaken as Congestion Status during Breast Reconstruction with Deep Inferior Epigastric Perforator Free Flap Coverage - Yoon Jae Lee; Hyun Jun Cho; Deuk Young Oh (Archives of Aesthetic Plastic Surgery, 2017)
We present the first reported case of cold urticaria, which was mistaken as congestion status, in a patient undergoing breast reconstruction with deep inferior epigastric perforator (DIEP) flap coverage. A 53-year-old woman underwent an immediate bilateral breast reconstruction with DIEP flap coverage. The harvested DIEP flap was wrapped with wet gauze and kept above an ice pack to minimize ischemic damage before flap in-setting to the mastectomy site. After the transfer of the harvested DIEP flap, she had suddenly developed an erythematous and edematous lesion, specifically on the flap. The room temperature was raised and a single dose of steroid and antihistamine was given intravenously. At the first instance, flap congestion was suspected; however, as the rash gradually spread throughout the body, we could deduce that it was cold urticaria. The erythematous rash and whirl resolved soon after receiving medication. Patients with known cold urticaria undergoing surgical procedures require several precautions (e.g., antihistamine, relatively warm operation room) to lessen the risk of severe reaction. Especially in patients with DIEP free flap, the lack of preoperative treatment could result in a pinkish flap due to urticaria, which could be mistaken by the surgeon as a congested flap.